EFFECT OF SOWING BY DIFFERENT SEEDING RATES ON QUALITATIV TTIATS OF FOUR WHEAT (Triticum aestivum L.) CULTIVAR SEEDS - & et al., Saudi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment was carried out at laboratories of Agriculture and Marshes College , University of Thi-Qar and at laboratories of agriculture college , university of Basra during 2013 - 2014 . The aim of this study was to identify the effect of the different seeding rates (80,100,120 and 140 kg.ha-1) on viability and quality characters of four wheat cultivars ( Abu-Ghraib, IPA – 99 , Al-fatih and Al-Iraq ) seeds . Factorial experiments in CRD was used with four replication in two factors . The results showed that there were significant differences between two factors of study and their interaction. The seeds produced from seeding rate 80 kg.ha-1 gave the higher averages of field emergence , standard germination , radical length , seedling dry weight and protein percentage ( 81.18 % , 91.03 % , 7.92 cm , 5.23 gm and 13.71 % ), respectively . The seeds produced from seeding rate 100 kg.ha-1 gave the higher averages of first count test and plumule length ( 74.35 % and 6.45 cm ), respectively . The seeds produced from seeding rate 120 kg.ha-1 gave the higher averages of carbohydrate percentage (61.27) . Al-Iraq seeds gave the higher averages of field emergence , first count test , standard germination , radical length , plumule length , seedling dry weight and carbohydrate percentage ( 86.23% , 72.68 % , 93.22% , 8.51 cm , 6.88 cm , 5.83 gm and 61.65% ) , respectively. Abu-Ghraib seeds gave the higher averages of protein percentage (13.94 ). Al-Iraq seeds produced from seeding rate 80 kg.ha-1 gave the higher averages of field emergence , radical length and seedling dry weight ( 89.14% , 8.87 cm and 6.65 gm ), respectively . Al-Iraq seeds that product from seed rate 100 kg.ha-1 gave the higher averages of first count test , standard germination and plumule length ( 79.00% , 95.98% and 7.83 cm ), respectively . Al-Iraq seeds that product from seed rate 120 kg.ha-1 gave the higher averages of carbohydrate percentage ( 61.92% ). Abu-Ghraib seeds that product from seed rate 100 kg.ha-1 gave the higher average of protein percentage(14.25).